IMPLEMENTASI KURIKULUM 2013 EDISI REVISI DALAM PEMBELAJARAN MEMBACA PUISI (STUDI KASUS DI KELAS X IPS 1 SMA NEGERI 1 KARANGANYAR) - Nofi Dian Sari; Budhi Setiawan; Yant Mujiyanto (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This research is a qualitative research with case study approach. The population in this study were class X students of SMA Negeri 1 Karanganyar. The research sample was students of class X IPS 1 with purposive sampling sampling technique. Data sources include events, informants, and documents. Data collection techniques such as observation, interview, and document analysis. The data validity test consists of triangulation of data sources, method triangulation, and informant review. Data analysis technique is interactive model of analysis. The results of this study include: (1) teachers' perceptions of the implementation of the Curriculum 2013 Revised Edition on learning to read poetry is good; (2) instructional planning is prepared in accordance with Permendikbud Number 22 Year 2016; (3) the implementation of reading poetry learning works well; (4) assessment of learning has not been done effectively; (5) obstacles in the form of: (a) limited face-to-face learning time in semester 2; (b) the implementation of a less effective learning assessment; (c) not all students have the talent to read poetry and students find it difficult to find the atmosphere of poetry; (d) subjectivity in assessing literary learning; (6) efforts in the form of: (a) providing structured and unstructured tasks; (b) the use of tasks in group discussion so that the assessment of poetry reading can still be carried out in its entirety; (c) students are required to frequently see references to reading poetry from youtube; d) making assessment criteria.